Personality subtypes and chest pain in patients with nonobstructive coronary artery disease from the TweeSteden Mild Stenosis study: mediating effect of anxiety and depression. (24th June 2015) - Mommersteeg, P.M.C.; Widdershoven, J.W.; Aarnoudse, W.; Denollet, J.
Abstract: Background: Patients presenting with chest pain in nonobstructive coronary artery disease (CAD, luminal narrowing <60%) are at risk for emotional distress and future events. We aimed to examine the association of personality subtypes with persistent chest pain, and investigated the potential mediating effects of negative mood states. Methods: Any chest pain in the past month was the primary outcome measure reported by 523 patients with nonobstructive CAD (mean age 61.4 years, SD = 9.4; 48% men), who participate in the TweeSteden Mild Stenosis (TWIST) observational cohort. Personality was categorized into a 'reference group', a high social inhibition ('SI only'), a high negative affectivity ('NA only') and a 'Type D' (NA and SI) group. Negative mood states included symptoms of depression and anxiety (Hospital Anxiety and Depression Scale) and cognitive and somatic depression (Beck Depression Inventory). The PROCESS macro was used to examine the relation between personality subtypes and chest pain presence, with the negative mood states as potential mediators. Results: Persistent chest pain was present in 44% of the patients with nonobstructive CAD. Type D personality (OR = 1.91, 95% CI 1.24–2.95), but not the 'NA only' (OR = 1.48, 95% CI 0.89–2.44) or the 'SI only' (OR = 0.93, 95% CI 0.53–1.64) group was associated with chest pain, adjusted for age and sex. Negative mood states mediated the association between personality and chest pain. Conclusions: Type D personality, but not negative affectivity or social inhibition, was related to chest pain in nonobstructive CAD, which was mediated by negative mood states.